A Ti / Nb co-doped layered double perovskite type oxygen electrode material, a preparation method and application thereof

CN121726431BActive Publication Date: 2026-10-16CHINA UNIV OF MINING & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202512025270.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-30
Publication Date
2026-10-16
Estimated Expiration
2045-12-30

AI Technical Summary

Technical Problem

然而,PBC在作为PCC氧电极的实际应用中仍存在明显不足,其材料自身的质子传导能力较低,制约了质子的体相迁移与反应位点,影响ORR/OER的催化能力,且其热膨胀系数较高,在电池长期运行或升降温过程中易引起电极与电解质之间的界面剥离

Benefits of technology

本发明制备得到的Ti/Nb共掺杂的层状双钙钛矿型氧电极材料在PrBaCo2O5+δ高本征活性的基础上,通过Ti/Nb双元素的掺杂,提升了材料的质子电导率、抑制元素偏析、降低热膨胀系数,使得氧电极材料具有高电催化活性与运行稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121726431B_ABST
    Figure CN121726431B_ABST
Patent Text Reader

Abstract

The application discloses a Ti / Nb co-doped layered double perovskite type oxygen electrode material and a preparation method and application thereof. 2‑x‑y Ti x Nb y O 5+δ , wherein 0 < x ≤ 0.2, 0 < y ≤ 0.2, and δ is an oxygen vacancy content. 5+δ The Ti / Nb co-doped layered double perovskite type oxygen electrode material prepared by the application has high intrinsic activity, and through Ti / Nb double-element doping, the proton conductivity of the oxygen electrode material is improved, element segregation is inhibited, and the thermal expansion coefficient is reduced, so that the oxygen electrode material has high electrocatalytic activity and operation stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic fuel cell technology, specifically relating to a Ti / Nb co-doped layered double perovskite oxygen electrode material, its preparation method, and its application. Background Technology

[0002] Proton ceramic cells (PCCs) are devices capable of efficiently and cleanly converting chemical energy into electrical energy. They can operate in both fuel cell and electrolyzer modes and are of great significance for building a future sustainable energy system. The oxygen electrode is one of the core components of PCCs, generally requiring excellent proton, oxygen ion, and electron transport capabilities. However, its high activation energies for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at relatively low temperatures (below 600℃) result in slow reactions and high polarization resistance, severely limiting the power generation efficiency or hydrogen evolution efficiency of PCCs.

[0003] Currently, cobalt-based perovskite materials are widely considered to be promising candidates for oxygen electrodes. Among them, the double perovskite PrBaCo2O with an ordered A-site structure is particularly promising. 5+δ Polycarbonate (PBC) has attracted widespread attention due to its excellent oxygen exchange and bulk transport properties. However, PBC still has significant shortcomings in practical applications as an oxygen electrode in polycarbonate (PCC). Its low proton conductivity restricts proton bulk migration and reaction sites, affecting the catalytic activity of oxygen exchanger (ORR) / electrolyte (OER). Furthermore, its high coefficient of thermal expansion makes it prone to interfacial delamination between the electrode and electrolyte during long-term battery operation or temperature fluctuations. In addition, PCCs generate water on the oxygen electrode side in fuel cell mode and require a water-containing atmosphere in electrolysis mode, but water vapor significantly accelerates the surface segregation and phase structure degradation of alkaline earth metals such as Ba, severely impairing the long-term stability of the electrode. Summary of the Invention

[0004] The purpose of this invention is to provide a Ti / Nb co-doped layered double perovskite oxygen electrode material, its preparation method, and its application. This layered double perovskite oxygen electrode material is based on PrBaCo2O 5+δ Based on high intrinsic activity, the doping of Ti / Nb dual elements improves the proton conductivity of the oxygen electrode material, suppresses elemental segregation, and reduces the coefficient of thermal expansion, thus giving the oxygen electrode material high electrocatalytic activity and operational stability.

[0005] To achieve the above objectives, this invention proposes a Ti / Nb co-doped layered double perovskite oxygen electrode material, characterized by having the general chemical formula PrBaCo. 2-x-y Ti x Nb y O 5+δ, where 0<x ≤ 0.2, 0<y ≤ 0.2, and δ is the oxygen vacancy content.

[0006] Preferably, the oxygen electrode material is PrBaCo 1.8 Ti 0.1 Nb 0.1 O 5+δ , where δ is the oxygen vacancy content.

[0007] To achieve the above objective, the present invention further proposes a preparation method of a Ti / Nb co-doped layered double perovskite type oxygen electrode material, comprising the following steps: S1. Weigh the raw material compounds containing Pr, Ba, Co, Ti and Nb according to the stoichiometric ratio of each element in the oxygen electrode material PrBaCo 2-x-y Ti x Nb y O 5+δ , dissolve them in deionized water to obtain a solution A; S2. Add citric acid and ethylenediaminetetraacetic acid as complexing agents to the solution A obtained in step S1 in sequence, add ammonia water to adjust the pH value, and heat and stir to evaporate water to form a black gel; S3. Transfer the black gel obtained in step S2 to an oven, heat and maintain the temperature to obtain a precursor material; S4. Grind the precursor material obtained in step S3, then place it in a muffle furnace, and calcine it in an air atmosphere to obtain the Ti / Nb co-doped layered double perovskite type oxygen electrode material.

[0008] Preferably, in step S1, the compounds containing Pr, Ba, Co, Ti and Nb are Pr(NO3)3·6H2O, Ba(NO3)2, Co(NO3)2·6H2O, C 16 H 36 O4Ti and ammonium niobium oxalate hydrate respectively.

[0009] Preferably, in step S2, the molar ratio of metal ions, citric acid to ethylenediaminetetraacetic acid is 1:2:1.

[0010] Preferably, in step S2, the pH value of the adjusted solution is 7 to 9, and the heating temperature is 80 to 90 °C.

[0011] Preferably, in step S3, the heating temperature of the oven is 250 to 300 °C, and the holding time is 5 to 10 h.

[0012] Preferably, in step S4, the heating process of the muffle furnace is as follows: the temperature is increased from room temperature to 600℃ at a heating rate of 3℃ / min and held for 2 hours, and then the temperature is increased from 600℃ to 1000~1200℃ at a heating rate of 2℃ / min and held for 3~5 hours.

[0013] This invention also proposes the application of a Ti / Nb co-doped layered double perovskite oxygen electrode material in the oxygen electrode of a reversible proton ceramic battery.

[0014] Preferably, the reversible proton ceramic battery includes an oxygen electrode layer, an electrolyte layer, and a hydrogen electrode support layer. The oxygen electrode material of the oxygen electrode layer is a Ti / Nb dual-doped layered double perovskite oxygen electrode material, and the electrolyte of the electrolyte layer is BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3–δ The hydrogen electrode support of the hydrogen electrode support layer is NiO-BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3–δ Where δ represents the oxygen vacancy content, and NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3–δ The weight ratio is 6:4.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: The Ti / Nb co-doped layered double perovskite oxygen electrode material prepared by this invention is used in PrBaCo2O 5+δ Based on high intrinsic activity, the doping of Ti / Nb dual elements improves the proton conductivity of the material, suppresses elemental segregation, and reduces the coefficient of thermal expansion, thus enabling the oxygen electrode material to have high electrocatalytic activity and operational stability.

[0016] This invention effectively synergistically regulates PrBaCo through Ti / Nb dual-element doping. 1.8 Ti 0.1 Nb 0.1 O 5+δ The proton transport capability, thermomechanical stability, and electrode-electrolyte interface reliability of PrBaCo materials make them ideal for applications such as... 1.8 Ti 0.1 Nb 0.1 O 5+δ The material simultaneously achieves a synergistic improvement in proton conduction capacity, electrocatalytic activity, and structural stability. Attached Figure Description

[0017] Figure 1 This is the XRD pattern of the layered double perovskite oxygen electrode material (PBCTN) in Embodiment 1 of the present invention; Figure 2 The chemical compatibility test results of the layered double perovskite oxygen electrode material (PBCTN) and electrolyte BZCYYb in Embodiment 1 of the present invention are as follows: Figure 3 It is the layered double perovskite oxygen electrode material (PBCTN) and PrBaCo2O in Embodiment 1 of this invention. 5+δ Fourier transform infrared spectrum of (PBC); Figure 4 It is the layered double perovskite oxygen electrode material (PBCTN) and PrBaCo2O in Embodiment 1 of this invention. 5+δ Thermal expansion curve of (PBC); Figure 5 It is the layered double perovskite oxygen electrode material (PBCTN) and PrBaCo2O in Embodiment 1 of this invention. 5+δ Polarization impedance comparison diagram of (PBC); Figure 6 It is the layered double perovskite oxygen electrode material (PBCTN) and PrBaCo2O in Embodiment 1 of this invention. 5+δ (PBC) Long-term test comparison chart; Figure 7 These are the performance curves of the PBCTN | BZCYYb | NiO-BZCYYb full cell in the power generation mode at 550~700 ℃ in Embodiment 1 of the present invention; Figure 8 These are the performance curves of the PBCTN | BZCYYb | NiO-BZCYYb full cell in Embodiment 1 of the present invention under electrolysis mode at 550~700 °C. Detailed Implementation

[0018] The invention will now be further described with reference to the accompanying drawings.

[0019] A method for preparing a Ti / Nb co-doped layered double perovskite oxygen electrode material includes the following steps: S1, Ti / Nb co-doped layered double perovskite oxygen electrode material PrBaCo 2-x-y Ti x Nb y O 5+δ The stoichiometric ratios of the elements in the sample are determined by weighing Pr(NO3)3·6H2O, Ba(NO3)2, Co(NO3)2·6H2O, and C. 16 H 36 O4Ti (tetrabutyl titanate) and C 10 H5NbO20 ·xH2O, first add C dropwise to deionized water while stirring vigorously. 16 H 36 O4Ti, then add Pr(NO3)3·6H2O, Ba(NO3)2, Co(NO3)2·6H2O and C 10 H5NbO 20 ·xH2O yields solution A, in which ammonium niobate oxalate hydrate is C. 10 H5NbO 20 ·xH2O.

[0020] S2. Citric acid and ethylenediaminetetraacetic acid are added sequentially to solution A from step S1 as complexing agents. The molar ratio of all metal ions, citric acid and ethylenediaminetetraacetic acid in solution A is 1:2:1. Then, ammonia is added to adjust the pH to 7-9. The mixture is stirred continuously at 80-90 °C until the water evaporates and a black gel is formed.

[0021] S3. Transfer the black gel from step S2 to an oven and perform self-propagating combustion at 250~300 ℃ for 5~10 h to obtain loose precursor ash, i.e. precursor material.

[0022] S4. After grinding the precursor material obtained in step S3, place it in a muffle furnace and calcine it in an air atmosphere. The muffle furnace is heated from room temperature to 600 ℃ at a heating rate of 3 ℃ / min and held at that temperature for 2 h. Then, the temperature is raised from 600 ℃ to 1000~1200 ℃ at a heating rate of 2 ℃ / min and held at that temperature for 3~5 h to obtain Ti and Nb co-doped layered double perovskite oxygen electrode material.

[0023] Example 1

[0024] The chemical formula is PrBaCo 1.8 Ti 0.1 Nb 0.1 O 5+δ The preparation steps of the Ti / Nb co-doped layered double perovskite oxygen electrode material are as follows: S1, Press PrBaCo 1.8 Ti 0.1 Nb 0.1 O 5+δ The stoichiometric ratio of the elements in the solution is 1:1:1.8:0.1:0.1. Weigh out 12.00 g of Pr(NO3)3·6H2O, 7.17 g of Ba(NO3)2, 14.45 g of Co(NO3)2·6H2O, and 0.94 g of C, respectively. 16 H 36 O4Ti and 0.83 g of C 10 H5NbO 20·xH2O, first add C dropwise to 200 mL of deionized water while stirring vigorously. 16 H 36 O4Ti, then add Pr(NO3)3·6H2O, Ba(NO3)2, Co(NO3)2·6H2O and C 10 H5NbO 20 ·xH2O, to obtain solution A.

[0025] S2. Add 34.61 g of citric acid and 32.08 g of ethylenediaminetetraacetic acid as complexing agents to solution A from step S1 in sequence. Then add ammonia water to adjust the pH to 7-8. Stir continuously at 80-90 °C until the water evaporates and a black gel is formed.

[0026] S3. Transfer the black gel from step S2 to an oven and perform self-propagating combustion at 300 °C for 8 h to obtain loose precursor ash, i.e., precursor material.

[0027] S4. After grinding the precursor material obtained in step S3, place it in a muffle furnace and calcine it in air. The muffle furnace is heated from room temperature to 600 ℃ at a heating rate of 3 ℃ / min and held at that temperature for 2 h. Then, the temperature is increased from 600 ℃ to 1050 ℃ at a heating rate of 2 ℃ / min and held at that temperature for 3 h to obtain the Ti / Nb co-doped layered double perovskite oxygen electrode material, namely PrBaCo. 1.8 Ti 0.1 Nb 0.1 O 5+δ (PBCTN) powder.

[0028] See appendix Figure 1 The image shows the XRD pattern of the PBCTN powder prepared in this embodiment. The results show that the characteristic diffraction peaks of the obtained pattern are consistent with those of PrBaCo2O. 5+δ The results (PDF#: 72-0937) are in perfect agreement, and no impurity phase diffraction peaks were detected, proving that a pure-phase A-site ordered layered double perovskite structure material was successfully synthesized.

[0029] To evaluate the chemical compatibility of the PBCTN material with the electrolyte, the PBCTN powder obtained in this example was mixed with BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb) electrolyte powder was uniformly mixed at a mass ratio of 1:1, calcined at 1100 ℃ for 10 h, and then subjected to XRD testing. The results are as follows: Figure 2As shown in the spectrum, only the characteristic diffraction peaks of PBCTN and BZCYYb are clearly visible, and no other impurity phase peaks appear, indicating that the two still maintain their respective crystal structures after high-temperature treatment and have good chemical stability and compatibility.

[0030] To further verify the improved hydration capacity of PBCTN materials, PrBaCo2O 5+δ (PBC) and PBCTN powders were treated at 600℃ in an air atmosphere with 30% H2O for 10 h, followed by Fourier transform infrared spectroscopy (FTIR) analysis. The results are as follows: Figure 3 As shown, in the range of 3200–3800 cm -1 Within the absorption peak region corresponding to the stretching vibration of the hydroxyl group (-OH), the peak area of ​​PBCTN is significantly larger than that of PBC. This indicates that PBCTN has superior hydration capacity and forms more proton defects in the material, thus providing direct evidence for its higher proton conductivity.

[0031] Add 3 wt% polyvinyl butyral (PVB) binder to PBCTN powder and add an appropriate amount of ethanol. Grind until the ethanol is completely evaporated to ensure that the powder and binder are mixed evenly. Weigh 1.5 g of the mixed powder and press it into a 3 mm × 4 mm × 10 mm rectangular sample strip under a pressure of 200 MPa for 2 min. Place it in a muffle furnace and heat it from room temperature to 600 °C at a heating rate of 2 °C / min, hold it at that temperature for 2 h, then heat it to 1250 °C at a heating rate of 2 °C / min and hold it for 5 h, then cool it down to 600 °C at a cooling rate of 2 °C / min, and finally let it cool naturally to room temperature to obtain a dense PBCTN sample strip.

[0032] The dense PBCTN sample strip obtained in this embodiment was placed in a thermal expansion apparatus, and its thermal expansion behavior in the temperature range of 25~800 ℃ was tested at a heating rate of 10K / min in air atmosphere. The results are as follows. Figure 4 As shown. Analysis and calculation show that the average coefficient of thermal expansion of PBCTN within the test temperature range is 17.8 × 10⁻⁶. -6 K -1 It is significantly lower than the 20.6 × 10⁻⁶ of PBC material. -6 K -1 This indicates that Ti / Nb dual doping effectively reduces the thermal expansion rate of the material, which helps to improve the thermal matching and interfacial bonding stability between the electrode and the electrolyte.

[0033] The obtained PBCTN powder was mixed with a binder (terpineol containing 5% wt ethyl cellulose) at a mass ratio of 1:1 to prepare an electrode paste. The paste was then screen-printed onto a dense BaZr substrate. 0.1 Ce 0.7 Y0.1 Yb 0.1 O 3-δ On the electrolyte sheet, the temperature is increased from room temperature to 600 ℃ at a rate of 3 ℃ / min and held for 2 h, then increased from 600 ℃ to 1000 ℃ at a rate of 2 ℃ / min and held for 3 h, and finally cooled naturally to room temperature to form a porous oxygen electrode with a thickness of about 10~15 μm.

[0034] The symmetrical cell was placed in an air atmosphere containing 3% H2O, and its polarization resistance at 700 °C was measured by electrochemical impedance spectroscopy. Its stability was then tested for 400 h at 650 °C in air containing 30% H2O. The impedance spectroscopy results are as follows: Figure 5 As shown, the polarization resistance of the PBCTN is 0.06 Ω·cm. 2 This is significantly lower than the 0.1 Ω·cm of PBC. 2 This indicates that PBCTN exhibits significantly enhanced electrocatalytic activity. Long-term stability test results are as follows: Figure 6 As shown, PBCTN maintains excellent electrochemical stability in high temperature and high humidity environments, and its impedance value does not decrease significantly throughout the entire test cycle, while PBC shows significant performance degradation, further proving that the Ti / Nb dual doping strategy effectively improves the durability of PBCTN in harsh environments.

[0035] Ni-BZCYYb | BZCYYb half-cells were prepared using phase inversion casting and spin coating techniques. PBCTN paste was screen-printed onto the dense electrolyte side of the half-cell. The temperature was increased from room temperature to 600 °C at a rate of 3 °C / min and held for 2 h, then increased from 600 °C to 1000 °C at a rate of 2 °C / min and held for 3 h. Finally, the temperature was allowed to cool naturally to room temperature, resulting in a Ni-BZCYYb | BZCYYb | PBCTN full cell.

[0036] Figure 7 The performance curves of the PBCTN | BZCYYb | NiO-BZCYYb full cell in the power generation mode at 550-700 ℃ are shown. The peak power densities at 700 ℃, 650 ℃, 600 ℃, and 550 ℃ are 1.12 W·cm³. -2 0.79 W·cm -2 0.52 W·cm -2 and 0.34 W·cm -2 . Figure 8The performance curves of the PBCTN | BZCYYb | NiO-BZCYYb full cell are shown in the electrolysis mode at 550-700℃. The current densities at an electrolysis voltage of 1.3 V at 700℃, 650℃, 600℃, and 550℃ are -3.1 A·cm⁻¹. -2 -1.9 A·cm -2 -1.1 A·cm -2 and -0.67 A·cm -2 .

[0037] The above are merely preferred embodiments of the present invention and do not constitute any limitation on the present invention. Any equivalent substitutions or modifications made by those skilled in the art to the technical solutions and content disclosed in the present invention without departing from the scope of the present invention shall be deemed to have remained within the protection scope of the present invention.

Claims

1. A Ti / Nb co-doped layered double perovskite oxygen electrode material, characterized in that, The general chemical formula is PrBaCo. 2-x-y Ti x Nb y O 5+δ Where 0 < x ≤ 0.2, 0 < y ≤ 0.2, and δ is the oxygen vacancy content; the oxygen electrode material is PrBaCo. 1.8 Ti 0.1 Nb 0.1 O 5+δ δ represents the oxygen vacancy content.

2. A method for preparing the Ti / Nb co-doped layered double perovskite oxygen electrode material as described in claim 1, characterized in that, Includes the following steps: S1, according to oxygen electrode material PrBaCo 2-x-y Ti x Nb y O 5+δ The stoichiometric ratio of each element is determined by weighing the raw material compound containing Pr, Ba, Co, Ti, and Nb, dissolving it in deionized water to obtain solution A. S2. Citric acid and ethylenediaminetetraacetic acid are added sequentially to solution A in step S1 as complexing agents, ammonia is added to adjust the pH, and the mixture is heated and stirred to evaporate the water and form a black gel. S3. Transfer the black gel from step S2 into an oven, heat and keep warm to obtain the precursor material; S4. After grinding the precursor material obtained in step S3, place it in a muffle furnace and calcine it in an air atmosphere to obtain Ti / Nb co-doped layered double perovskite oxygen electrode material.

3. The method for preparing a Ti / Nb co-doped layered double perovskite oxygen electrode material according to claim 2, characterized in that, In step S1, the compounds containing Pr, Ba, Co, Ti, and Nb are Pr(NO3)3·6H2O, Ba(NO3)2, Co(NO3)2·6H2O, and C, respectively. 16 H 36 O4Ti and ammonium niobate oxalate hydrate.

4. The method for preparing a Ti / Nb co-doped layered double perovskite oxygen electrode material according to claim 2, characterized in that, In step S2, the molar ratio of metal ions, citric acid, and ethylenediaminetetraacetic acid is 1:2:

1.

5. The method for preparing a Ti / Nb co-doped layered double perovskite oxygen electrode material according to claim 2, characterized in that, In step S2, the pH of the solution is adjusted to 7-9, and the heating temperature is 80-90 ℃.

6. The method for preparing a Ti / Nb co-doped layered double perovskite oxygen electrode material according to claim 2, characterized in that, In step S3, the heating temperature of the oven is 250~300 ℃, and the holding time is 5~10 h.

7. The method for preparing a Ti / Nb co-doped layered double perovskite oxygen electrode material according to claim 2, characterized in that, In step S4, the heating process of the muffle furnace is as follows: the temperature is increased from room temperature to 600 ℃ at a heating rate of 3 ℃ / min and held for 2 h, and then the temperature is increased from 600 ℃ to 1000~1200 ℃ at a heating rate of 2 ℃ / min and held for 3~5 h.

8. The application of the Ti / Nb co-doped layered double perovskite oxygen electrode material as described in claim 1 in the oxygen electrode of a reversible proton ceramic battery.

9. The application according to claim 8, characterized in that, The reversible proton ceramic battery includes an oxygen electrode layer, an electrolyte layer, and a hydrogen electrode support layer. The oxygen electrode material of the oxygen electrode layer is a Ti / Nb dual-doped layered double perovskite oxygen electrode material. The electrolyte of the electrolyte layer is BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3–δ The hydrogen electrode support of the hydrogen electrode support layer is NiO-BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3–δ Where δ represents the oxygen vacancy content, and NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3–δ The weight ratio is 6:4.

Citation Information

Patent Citations

  • Doping type biphase oxygen electrode material based on in-situ reconstruction and preparation method and application thereof

    CN120999019A